BLOOD DESCRIPTION OF STRIPED CATFISH (Pangasianodon hypophthalmus) MAINTAINED BY AQUAPONIC SYSTEM AND PHOTOPERIOD MANIPULATION - Saputra, Raja Darmawan; Siregar, Morina Riauwaty; Windarti, Windarti (Asian Journal of Aquatic Sciences, 2022)
Environmental conditions and nutrient input greatly affect the physiological condition of fish. The growth of Pangasianodon hypophthalmus is improved by rearing it in short photoperiod. To maintain fish health, water quality must be maintained by applying aquaponics. The application of an aquaponic system can maintain water quality. To understand the blood condition of P.hypophthalmus reared in an aquaponic system and manipulated of photoperiod has been conducted in June-August 2021. The fish was reared in a bucket of 100 L water, 30 fishes/bucket (6-8 cm TL). Treatment with aquaponics system and filters as well as 24-hour dark photoperiod and natural photoperiod. The parameters measured were the erythrocytes total, leukocytes total, hematocrit, leukocrit, and leukocyte differential of P. hypophthalmus. The result showed that in general the blood condition of the fish there was no abnormality. Differentiation leukocytes are still relatively normal. The blood condition of all fish treated were erythrocyte total was 1.76-1.85 x106 cells/mm3, leucocyte was 5.45-5.66 x104 cells/mm3, hematocrit were 21.3-37.2% and leukocrit were 0.5-1 %. Based on the data obtained, it can be concluded that with aquaponic system and manipulated photoperiod do not negatively affect the health status of fish in general.